Endodontic Treatment of Type II Dens Invaginatus in a Maxillary Lateral Incisor: A Case Report - Dilek Helvacioglu-Yigit; Seda Aydemir (Hindawi Limited, 2012)
Dens invaginatus is a developmental anomaly that results in an enamel-lined cavity intruding into the crown or root before the mineralization phase. It typically affects permanent maxillary lateral incisors, central incisors, and premolars. This paper describes the root canal treatment of Oehlers' type II dens invaginatus in maxillary left lateral incisors. A 16-year-old boy presented to the Faculty of Dentistry, University of Kocaeli, to receive his dental treatments. During the caries removal, the pulp was exposed then anendodontic treatment was initiated. Two canals, one of which represented the invagination, were instrumented, irrigated, and then obturated with a lateral condensation technique.